Employee Motivation and Perceptions toward the Importance of Hospital Accreditation on Service Commitment at Pelita Insani Martapura Hospital - Karyono, Septin Maisharah; Peristiowati, Yuly; Suhita, Byba Melda (Journal of Health Policy and Management, 2021)
Background: Hospital accreditation is a form of appreciation for hospital organizations that have met the service standards set by the government. Perceptions and motivations about the importance of accreditation for hospital institutions and employees are needed to foster a sense of service commitment in employees for the realization of a quality service system. The purpose of this study was to determine the relationship between perceptions of the importance of Hospital Accreditation with participation, commitment, job satisfaction, and employee performance.Subjects and Method: A cross sectional study was conducted at Pelita Insani Martapura Hospital, South Kalimantan, Indonesia. The research population is hospital employees. The sample is 153 hospital employees selected by proportional random sampling. The dependent variable is work commitment. The independent variables are perceptions of the importance of accreditation and motivation. Data were collected using observation sheets and questionnaires and analyzed by multiple linear regression.Results: High perception about the importance of accreditation (b= 0.06; 95% CI= 0.02 to 0.13; <0.001) and strong motivation (b= 0.31; 95% CI= 0.31 to 0.71; p= 0.006) increased employee commitment.Conclusion: High perception of the importance of accreditation and strong motivation to increase employee work commitment.Keywords: commitment, perception, motivation, accreditationCorrespondence: Septin Maisharah Karyono. Strada Indonesian Health Sciences Institute, Kediri, Indonesia.Journal of Health Policy and Management https://doi.org/10.26911/thejhpm.2021.06.03.05.